2018
DOI: 10.26418/jpmipa.v9i1.23693
|View full text |Cite
|
Sign up to set email alerts
|

Meningkatkan Partisipasi Aktif Mahasiswa Melalui Lesson Study Pada Mata Kuliah Geometri Ruang

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Students actively involved in learning will gain more experience and knowledge (Untarti & Kusuma, 2018). The higher the active participation of students in learning, the more impact on teaching and learning activities more lively and meaningful (Safitri, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Students actively involved in learning will gain more experience and knowledge (Untarti & Kusuma, 2018). The higher the active participation of students in learning, the more impact on teaching and learning activities more lively and meaningful (Safitri, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that GeoGebra is able to have a positive impact on students' understanding of concepts (Kurniasih, Wiyanti, & Zahid, 2018;Lestari, 2018;Mudaly & Fletcher, 2019). Likewise, some studies have also tried to design space geometry learning, but no one has yet used GeoGebra to apply it to the course (Untarti & Kusuma, 2018;Wahyuni & Rahmadhani, 2019).…”
Section: Introductionmentioning
confidence: 99%